Rhythm and Meter in the Early Juan Ramón Jiménez: The Case of "¡Silencio!" of Estío - Vialla Hartfield-Méndez (Studies in 20th & 21st Century Literature, 1994)
The literary trajectory of Juan Ramón Jiménez is commonly divided into two periods, though this division is also generally recognized as an oversimplification of a very complex process in which the poet moves from the use of more traditional poetic forms, and a more concrete reference to reality, to the practice of free verse and more metaphysical expressions of man's relationship to his surroundings. "¡Silencio!," the last poem of Estío (1915), was written just prior to Diario de un poeta reciéncasado, the book with which it is considered that Juan Ramón began the second stage of his literary trajectory. "¡Silencio!" is a pivotal poem which presents various elements of nature that had appeared in Juan Ramón's earlier poetry, but in a new context, clearly anticipating in form and content what was to be Juan Ramón's next poetic enterprise. The "eternal silence" of the poem's last line is a transcendental silence that is the ultimate goal of his poetry. A close structural analysis of the poem reveals the manner in which Juan Ramón identifies transcendental qualities that he finds within himself with the various elements of Nature, and thus anticipates the totality of being that he seemed to achieve in his later works.
Keywords: Juan Ramón Jiménez; silencio; transcendent; poetry; nature; being; transcendency; Spanish poetry